Protein biomarkers in vernix with potential to predict the development of atopic eczema in early childhood. Issue 1 (11th November 2013) - Holm, T.; Rutishauser, D.; Kai‐Larsen, Y.; Lyutvinskiy, Y.; Stenius, F.; Zubarev, R. A.; Agerberth, B.; Alm, J.; Scheynius, A.
Abstract Background Atopic eczema (AE) is a chronic inflammatory skin disease, which has increased in prevalence. Evidence points toward lifestyle as a major risk factor. AE is often the first symptom early in life later followed by food allergy, asthma, and allergic rhinitis. Thus, there is a great need to find early, preferentially noninvasive, biomarkers to identify individuals that are predisposed to AE with the goal to prevent disease development. Objective To investigate whether the protein abundances in vernix can predict later development of AE. Methods Vernix collected at birth from 34 newborns within the Assessment of Lifestyle and Allergic Disease During INfancy (ALADDIN) birth cohort was included in the study. At 2 years of age, 18 children had developed AE. Vernix proteins were identified and quantified with liquid chromatography coupled to tandem mass spectrometry. Results We identified and quantified 203 proteins in all vernix samples. An orthogonal projections to latent structures‐discriminant analysis (OPLS‐DA) model was found with R2 = 0.85, Q2 = 0.39, and discrimination power between the AE and healthy group of 73.5%. Polyubiquitin‐C and calmodulin‐like protein 5 showed strong negative correlation to the AE group, with a correlation coefficient of 0.73 and 0.68, respectively, and a P‐value of 8.2 E‐7 and 1.8 E‐5, respectively. For these two proteins, the OPLS‐DA model showed a prediction accuracy of 91.2%. Conclusion The protein abundances in vernix, and particularly that of polyubiquitin‐C and calmodulin‐like protein 5, are promising candidates as biomarkers for the identification of newborns predisposed to develop AE.